The Role of the Central Bank in Monetary Stability: Iraq as a Case Study (2004-2024) - Tomas, Haqi (Indonesian Journal Publisher, 2026)
This research aims to address a highly important issue, which is monetary stability, a goal pursued by most of the world's economies. When monetary stability is achieved, development can accelerate significantly due to the absence of economic problems such as inflation, unemployment, and others. The study also examines the role that the central bank can play through monetary policy tools in achieving the desired monetary stability. It addressed the emergence of central banks and their development stages, as well as identifying their key characteristics, objectives, and functions. The study also examined monetary stability, its importance, and introduced its main indicators, along with how to calculate monetary stability indicators. Furthermore, the study covered the establishment of the Central Bank of Iraq, its development stages, objectives, major achievements, and how monetary policy tools are used by the central bank in Iraq to influence monetary stability and attempt to support this stability. Finally, the indicators of monetary stability and the monetary excess index in Iraq for the period (2004–2024) were calculated, and many conclusions were reached, as well as several important recommendations were established to achieve monetary stability.